Enhancing knowledge and awareness of biosecurity practices for control of African swine fever among smallholder pig farmers in four districts along the Kenya–Uganda border - Nantima, Noelina; Davies, J.; Dione, Michel M.; Ocaido, M.; Okoth, Edward A.; Mugisha, A.; Bishop, Richard P. (Springer, 2016)
A study was undertaken along the Kenya–Uganda border in four districts of Tororo and Busia (Uganda) and Busia and Teso (Kenya) to understand smallholder farmers’ knowledge, practices and awareness of biosecurity measures. Information was collected by administering questionnaires to 645 randomly selected pig households in the study area. In addition, focus group discussions were carried out in 12 villages involving 248 people using a standardized list of questions. The outcome suggested that there was a very low level of awareness of biosecurity practices amongst smallholder farmers. We conclude that adoption of specific biosecurity practices by smallholder farmers is feasible but requires institutional support. There is a clear requirement for government authorities to sensitize farmers using approaches that allow active participation of farmers in the design, planning and implementation of biosecurity practices to enable enhanced adoption.